Peran guru pustakawan dalam pengelolaan koleksi cetak pada perpustakaan sekolah di Kecamatan Rejotangan Kabupaten Tulungagung - Pratama, Bagas Aldi; Masruri, Anis (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The school library is an important component for schools in supporting the teaching and learning process. The main function of the school library is as a manager and provider of collections to meet the information needs of users. This research aims to determine the role of teacher librarians in managing collections in school libraries. Research locations are the libraries of SMPN 1 Rejotangan, MTsN 3 Tulungagung, SMAN 1 Rejotangan and SMKN 1 Rejotangan. This location was chosen because the teacher librarian is the manager of the school library. This research method uses a descriptive qualitative approach with data search techniques through observation, interviews and documentation. The research results show that the role of teacher librarians is still not effective and efficient in managing collections. Of the four schools, the number of librarian teachers, duties, programs and strategies for managing collections are different. Starting from procurement, processing to maintaining collections in different ways. Procurement of collections by adjusting the information needs of teachers and students from the school budget. Some classification systems do not yet use DDC and some do. Catalog system with cards to online like OPAC. Collection maintenance by covering books, cleaning dust, and carrying out repairs on collections that experience minor damage. Apart from managing the library, teacher librarians also have the task of teaching students in class. Teacher librarians have difficulty managing collections due to a lack of understanding of the material. Considering these problems, teacher librarians need to take part in librarian training regularly.